2016
DOI: 10.1007/s11356-016-7560-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of several leaching reagents on removal of Cu, Pb, Cd, and Zn from highly contaminated paddy soil

Abstract: The efficiency of five different single leaching reagents (tartaric acid (TA), citric acid (CA), CaCl, FeCl, EDTA) and two different composite leaching reagents (CA + FeCl, CA + EDTA) on removing Cu, Pb, Zn, and Cd from contaminated paddy soil in Hunan Province (in China) was studied. The results indicated that the efficiencies of CA, FeCl, and EDTA on extracting Cu, Pb, Cd, and Zn from soil were greater than that of TA and CaCl, and their extraction efficiencies were EDTA ≥ FeCl > CA. The efficiencies of CA +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 44 publications
1
4
0
1
Order By: Relevance
“…Udovic and Lestan reported that the removal of labile heavy-metal species from the soil would disturb the chemical equilibrium among different species, thus potentially re-establishing such an equilibrium and shifting heavy metals back to more available chemical forms [25]. Gao et al reported that the easily reducible and oxidizable fractions of Cd were transformed into easily extractable fractions after the soil was leached by the composite reagents with citric acid and FeCl 3 [16]. Thus, Cd bound to Fe-Mn oxides might have undergone this transformation during the washing process and been removed by FeCl 3 or HCl in this study.…”
Section: Effects Of Ferric Chloride On CD Extraction Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Udovic and Lestan reported that the removal of labile heavy-metal species from the soil would disturb the chemical equilibrium among different species, thus potentially re-establishing such an equilibrium and shifting heavy metals back to more available chemical forms [25]. Gao et al reported that the easily reducible and oxidizable fractions of Cd were transformed into easily extractable fractions after the soil was leached by the composite reagents with citric acid and FeCl 3 [16]. Thus, Cd bound to Fe-Mn oxides might have undergone this transformation during the washing process and been removed by FeCl 3 or HCl in this study.…”
Section: Effects Of Ferric Chloride On CD Extraction Efficiencymentioning
confidence: 99%
“…Above an extraction pH of 2.4, FeCl 3 could extract soil Cd more effectively than HCl [13]. Gao et al, using leaching experiments, reported that 20 mmol•L −1 FeCl 3 removed 66.5% Cd from a contaminated paddy soil in Hunan Province, China [16]. Although FeCl 3 is a promising washing reagent, it is not clear whether it causes damage to the soil structure, an important factor for crop cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metal cations released into the environment with industrial and farming pollution sources, such as chemicals and fertilizers, often result in an increase in heavy metal concentrations in water resources and may ultimately accumulate through the food chain and pose a grave danger to both human health and ecological security [ 1 ]. Since heavy metals cannot be biodegraded and will not be eliminated through chemical processes, they may move, transform and/or accumulate in water bodies or soil [ 2 ]. Due to their distinguishing features and speciation transformation, for metals such as Hg and Pb, and concentration passivation, for metals such as Cd and Cu, contamination caused by heavy metal cations has become an area of increasing concern in the research field [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies are concentrated on the passivation of heavy metals in soils, the knowledge about the state of heavy metals in real field conditions is limited. Weather, soil permeability, depth of contamination, and especially the potential deep leaching of chemicals need more consideration [24][25][26]. The long-term effect of passivating agents on the passivation of heavy metals in the soil and its stability under natural precipitation conditions is still questioned [27,28].…”
Section: Introductionmentioning
confidence: 99%